Factors Affecting Thyroid Hormone Changes Over 1 Month After Birth in Preterm Newborns - Kim, Seulki (J Endocr Soc, 2021)
Purpose: To analyze factors affecting thyroid hormone changes over 1 month after birth in preterm newborns. Methods: Thyroid hormones, including free thyroxine (fT4) and thyroid stimulating hormone (TSH) of 216 preterm newborns (mean gestational age [GA] 33.6±2.6 weeks), were retrospectively reviewed at the 1(st) and 4(th) weeks after birth. Preterm newborns were classified into three groups according to the GA (< 28 weeks, group A; 28-32 weeks, group B; 32-36 weeks, group C). The association between thyroid hormone changes and clinical factors was analyzed. Results: Preterm newborns with older GA had higher concentrations of fT4 (group A, 0.9±0.2 ng/dL; group B, 1.2±0.2 ng/dL; group C, 1.5±0.3 ng/dL) and TSH (group A, 2.7±3.2 mIU/L; group B, 4.5±3.3 mIU/L; group C, 6.0±3.8 mIU/L), both at the 1(st) week after birth. fT4 and TSH at the 1(st) week after birth were positively correlated with the GA (r=0.52, P=0.0001; r=0.30, P=0.0001) and Apgar score at 5 minutes (r=0.31, P=0.0001; r=0.28, P=0.0001). TSH concentration at the 1(st) week after birth was significantly lower in the abnormal brain sonogram group than in the normal brain sonogram group (4.4±3.7 vs 6.1±3.4 mIU/L, P=0.001); there were no differences at the 4(th) week after birth between these groups (4.2±2.6 vs 3.4±2.4 mIU/L, P=0.485). Multiple linear regression analysis revealed that GA was positively correlated with fT4 and TSH at the 1(st) week, and fT4 at 4(th) week after birth (B=0.08, SE=0.12, P=0.0001; B=0.34, SE=0.15, P=0.029; B=0.02, SE=0.01, P=0.013). Conclusion: Thyroid hormone levels in preterm newborns are mostly within the normal reference value of full-term newborns within 4 weeks of life, and are mainly affected by GA and brain ultrasound abnormalities.